2021
DOI: 10.1186/s12913-021-06864-9
|View full text |Cite
|
Sign up to set email alerts
|

Nurse practitioner led model of after-hours emergency care in an Australian rural urgent care Centre: health service stakeholder perceptions

Abstract: Background The challenges of providing and accessing quality health care in rural regions have long been identified. Innovative solutions are not only required but are also vital if effective, timely and equitable access to sustainable health care in rural communities is to be realised. Despite trial implementation of some alternative models of health care delivery, not all have been evaluated and their impacts are not well understood. The aim of this study was to explore the views of staff and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…Most sources described NPs in terms of the educational and practice requirements necessary for endorsement by the Nursing and Midwifery Board of Australia 16,18,29–34 . They conceptualised NPs' role in terms of their scope of practice 8,16,29,30,33–36 . Other sources noted the potential of NPs to improve health care access, health outcomes and consumer satisfaction within rural health services 30 address service gaps 14,32 ; and adapt to changing community needs 14 …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Most sources described NPs in terms of the educational and practice requirements necessary for endorsement by the Nursing and Midwifery Board of Australia 16,18,29–34 . They conceptualised NPs' role in terms of their scope of practice 8,16,29,30,33–36 . Other sources noted the potential of NPs to improve health care access, health outcomes and consumer satisfaction within rural health services 30 address service gaps 14,32 ; and adapt to changing community needs 14 …”
Section: Resultsmentioning
confidence: 99%
“…The review revealed that NPs were working in community mental health and drug and alcohol services 8,31,34 ; at remote Aboriginal Medical Services 37 and Aboriginal Community Controlled Health Services 39 ; primary care in rural and remote locations 32,37,38 ; providing nurse‐led assessment and treatment centres and community‐based clinics 20,21,30,36,41,42 ; providing specialist aged care 35 and psychogeriatric services 8 ; NP locum services 14 ; and palliative care 33 . Some NPs worked across multiple health care settings, for example across hospital, residential aged care, general practice and community health 8,41 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations